2001
DOI: 10.1046/j.1464-410x.2001.02182.x
|View full text |Cite
|
Sign up to set email alerts
|

Histopathological mapping of open testicular biopsies in patients with unobstructive azoospermia

Abstract: Objective To evaluate, in patients with unobstructive azoospermia, the heterogeneity of spermatogenesis within the testes and thus whether there is any region of advanced spermatogenesis. Patients and methods Seventy infertile men (mean age 34 years, SD 5.01) with no varicoceles or testicular atrophy had bilateral open testicular biopsies taken from six different sites. For each biopsy specimen the number of seminiferous tubules and of tubules with sperm maturation were counted (by light microscopy at r 400). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 18 publications
(21 reference statements)
2
6
0
Order By: Relevance
“…[16], [21][27] In men with NOA, the success rates have been significantly lower, from 25–50% [21], [22], [28], but are improved when increasing the sample area [29][31]. Our experience using fresh and frozen TESE sperm in ICSI cycles was consistent with prior reports in regard to sperm recovery and fertilization outcomes.…”
Section: Discussionsupporting
confidence: 86%
“…[16], [21][27] In men with NOA, the success rates have been significantly lower, from 25–50% [21], [22], [28], but are improved when increasing the sample area [29][31]. Our experience using fresh and frozen TESE sperm in ICSI cycles was consistent with prior reports in regard to sperm recovery and fertilization outcomes.…”
Section: Discussionsupporting
confidence: 86%
“…The finding of normal spermatogenesis in the presence of Ychromosome microdeletions is an extremely rare finding, which has been previously reported by Pryor et al [35] to be associated with spermatic duct obstruction. The possibility of areas of focal spermatogenesis in the presence of testicular pathologies [36] may explain this finding. Our findings support the view that the worst spermatogenic defects are caused by deletions of the AZFa region [37].…”
Section: Discussionmentioning
confidence: 81%
“…In a later series of 628 men who had NOA undergoing 784 TESE procedures, the overall retrieval rate was 48%; 41.6% were successful on the first attempt [25]. Most practitioners agree that multiple random biopsies are likely to yield poorer results than the more directed biopsy (as discussed in the following section) and remove more tissue [34]. In addition, the risk of side effects may be amplified after random biopsies.…”
Section: Random Biopsiesmentioning
confidence: 99%
“…These imaging modalities detect a difference in blood flow, with areas of increased perfusion being the most likely to contain more advanced spermatogenesis, thereby directing the surgeon to the most likely sites of sperm production. Other studies investigated whether specific areas within the testis (eg, near the hilum) are more or less likely to contain sperm and found that there is no area that is more or less likely to yield mature sperm [34,39].…”
Section: Multiple Directed Biopsiesmentioning
confidence: 99%